Over 'Engels Hout' en 'boordbedden': het spanningsveld tussen uitheemse en inheemse beplanting (Bulletin KNOB, 2003)
In the eighteenth century European 'Grand Tourists', young men from well-to do families who made a cultural tour round Europe for educational purposes, brought all sorts of ideas back to their native country. These were materialised in an Arcadian, 'natural' landscape in the form of small-scale fragile architecture. In short, grottoes, temples, pavilions and cupolas with adjectives such as Greek, Turkish, Tartarian, Swiss and Chinese.Thus 18th-century people created a micro-cosmos in which both in terms of space and of time the whole world could be travelled during one single walk. Building and planting had to reinforce one another's character: red and green would thus be combined to form a paradisiacal Shangri-La, the unattainable Utopia.The 'new' Garden Art, the Arts' youngest sister, became the intermediary, transforming the boring, predictable, geometrical gardens and parks into inspired and 'picturesque' places with green, hilly landscapes and mysterious, apparently infinite, winding brooks. The park in 'English' landscape style became the ideal place to unite dream and reality. It emerged that the plant names from preserved planting lists of 18th and 19th-century garden and landscape architects did not correspond to the current terminology.As the knowledge on other elements of the history of country estates was increasing, the problem of the fading and erosion of the planting was becoming ever more urgent. What is required is attention for the materials those parks are composed of, notably the historical assortment of trees, shrubs and flowers, in combination with the architecture defining the character and the value of the monumental green.It is clear that a dendrological approach to the planting in historical gardens and parks is still in its infancy. Almost daily important exotic or native specimens are lost. This concerns trees and shrubs which are not only of inestimable value because of their special.